Individual Characteristics, Work–Life Balance, And Organizational Culture in Shaping Employee Performance: Evidence from The Penarungan Village Office, Badung, Bali - Ni Komang Ayu Puspita Dewi; Ni Nyoman Ari Novarini; Sapta Rini Widyawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
Individuals who have high productivity and play a major role in an organization, whether in an institutional or corporate environment, are referred to as human resources (HR). In this context, HR is considered a valuable asset to the organization. The purpose of this research is to analyze and explain the relationship between individual characteristics, work-life balance, and organizational culture on employee performance. This research was conducted at the Penarungan Badung Village Office. The background of this research is based on the research gap in previous studies and the differences in the focus of discussion related to the three variables. In addition, the issue of employee absenteeism fluctuations at the Penarungan Badung Village Office, with an average of 3.99% in 2023, also prompted this quantitative research with 32 respondents. The data obtained through questionnaires were analyzed using multiple linear regression, correlation and determination coefficient analysis, and hypothesis testing (F-test and t-test). The findings of the study consistently show that individual characteristics, work-life balance, and organizational culture each have a positive and significant effect on employee performance at the Penarungan Badung Village Office.